2014
DOI: 10.1007/s11764-014-0406-y
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship care planning and its influence on long-term patient-reported outcomes among colorectal and lung cancer survivors: the CanCORS disease-free survivor follow-up study

Abstract: PURPOSE Evaluate the relationship between survivorship care planning (SCP) and survivorship care and health outcomes reported by long-term lung and colorectal cancer survivors. METHODS Participants (n=832) were diagnosed and enrolled during 2003-2005. In 2012, patient-reported outcomes (survivorship care and health outcomes) and two patient-reported SCP measures (receipt of written summary of cancer treatment and receipt of instructions on who to see for routine cancer follow-up) were collected. Analyses con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…Consistent with previous estimates, Health Information National Trends Survey data suggest that receipt of treatment summaries is relatively low, with just over a third of survivors reporting having received these documents at the end of their cancer treatment 10,22,23 . Survivors’ demographic characteristics did not predict receipt of treatment summaries.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Consistent with previous estimates, Health Information National Trends Survey data suggest that receipt of treatment summaries is relatively low, with just over a third of survivors reporting having received these documents at the end of their cancer treatment 10,22,23 . Survivors’ demographic characteristics did not predict receipt of treatment summaries.…”
Section: Discussionsupporting
confidence: 82%
“…This research adds to the growing, albeit limited, body of evidence that treatment summaries, ideally as part of a comprehensive survivorship care plan, are associated with positive outcomes 10,23 . As new mandates increase the prevalence of treatment summaries 5 , we must continue to carefully examine their impact on clinical communication.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Integrating self-management coaching and its principles to communicate TS/CP content may help to alleviate uncertainty and promote a sense of control (Baravelli et al, 2009). Findings from the Cancer Care Outcomes Research and Surveillance Consortium (CanCORS) study of long-term colorectal and lung cancer survivors suggest that survivors who received care planning were more likely to have positive self-efficacy and to have seen a physician for follow-up care (Chrischilles et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…However, other studies found that CRC survivors experience significant levels of anxiety and distress (D’Souza et al, 2016). Studies show that SCP may lead to improved follow-up care, better long-term physical well-being, positive self-efficacy, improved survivor knowledge on survivorship care, and positive lifestyle changes (Chrischilles et al, 2015; Klemanski et al, 2016; Nissen et al, 2013). The qualitative data also provided support for improved self-efficacy and confidence in understanding their health plan going forward.…”
Section: Discussionmentioning
confidence: 99%